PROBLEMATIKA KONSEP, KEBIJAKAN DAN KELEMBAGAAN: PEMBERDAYAAN BURUH MIGRAN PEREMPUAN JAWA TIMUR - Suartina, Tine (Jurnal Masyarakat dan Budaya, 2013)
East Java Province is one of the top provinces in Indonesia that send migrant workers, including women migrant workers. That condition makes this province has many aspects related with the issues of women migrant worker. Empowerment of the migrant worker, including for women,is important since it contributes directly to the welfare of the workers. However, there are somedrawbacks, such as institutional construction, to address the empowerment of migrant workers in general and particularly, woman migrant workers.Another problem is about the arrangement concept that applied in the empowerment scheme. This article based on 2010 field research, focuses on empiricalconditions of empowerment activities and its implications, which influence women migrant worker.This article exposes Tulungagung Region’s experience to explore the understanding on women problems of empowerment in local arrangement.Keywords: East Java, Tulungagung Region, empowerment,women migrant worker.